Flame and shock wave evolution characteristics of methane explosion in a closed horizontal pipeline filled with a three-dimensional mesh porous material. (1st December 2022) - Yuan, Bihe; He, Yunlong; Chen, Xianfeng; Ding, Qingquan; Tang, Yi; Zhang, Yuduo; Li, Yi; Zhao, Qi; Huang, Chuyuan; Fang, Quan; Wang, Liancong; Jin, Hang
Abstract: In the energy security field, porous materials are regarded as superb explosive attenuators that quench flames and dissipate explosion energy waves. Traditional porous materials based on polymer have been extensively explored for their flame and explosion-proof capabilities, but their applications are limited due to the lack of indispensable physical properties such as flame-retardant and antistatic properties. The polymer composites may contaminate the oil medium, as does the deterioration of their properties. By designing the material's structure and formula, a new three-dimensional mesh porous flame and explosion-proof material (TFEP) is developed through melt blending—extrusion spinning technology and material's explosion-proof performance will also be enhanced. This porous material integrates flame-retardant, antistatic, and oil-resistant performances. The TFEP's suppression effect on 9.5 vol% CH4 /air premixed gas explosion was investigated under various filling conditions, and the optimal filling condition of TFEP was explored. Under these conditions, TFEP completely quenches the explosion flame, and the maximum explosion overpressure decay ratio for the upstream and downstream of the pipeline are 87.5% and 82.5%, respectively. TFEP eliminates the electrostatic risk generated by long-term friction of traditional polymer materials. It has moderate oil resistance and may be a candidate for explosion-proof materials in the fuel oil field. Graphical abstract: Image 1 Highlights: TFEP has an excellent flame and explosion-proof effect. The flame and explosion-proof mechanisms of TFEP were explored. TFEP can be a candidate for explosion-eproof material in fuel oil field.